Satellite phased arrays for direct-to-handset satellite: key technologies and future vision - JIAO Lingxiao; LI Wenjing; TONG Jianfei; LI Jifeng (Dianxin kexue)
To address the long distance and significant loss in satellite-to-ground wireless link, new demands are imposed on satellite phased arrays by direct-to-handset satellite. By analyzing the practical requirements of direct-to-handset satellite, the advantages and disadvantages of various beamforming architectures were outlined, then the proper selection strategy of beamforming architecture was proposed. Subsequently, dual-band shared-aperture circularly-polarized antenna arrays under frequency division duplexing (FDD) were discussed. In addition, the stacking and integration architecture of phased arrays was reviewed, and several key fabrication technologies for components and chips were introduced. Finally, the outlook and key technologies of satellite phased arrays for direct-to-handset satellite were presented.